THE IMPACT OF CHANGES IN MINERAL PRICES ON MINING EFFICIENCY - Murodov , Abbos (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
In a market economy, fluctuations in mineral prices directly affect the efficiency of mining development. This study theoretically analyzes the impact of price dynamics on the economic indicators of mining projects, particularly Net Present Value (NPV) and Internal Rate of Return (IRR). Furthermore, the research scientifically highlights the increase in investment risks and uncertainties in evaluating mining projects under conditions of price volatility.